1989
DOI: 10.1139/f89-287
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Abundance of Young Atlantic Cod (Gadus morhua) and Haddock (Melanogrammus aeglefinus) as Indicators of Year-class Strength

Abstract: To identify the life history stage(s) most influential in determining yearclass strength, we constructed and analyzed survival curves of the 1983, 1984, and 1985 cohorts of cod and haddock off Southwest Nova Scotia relative to their physical and biological environment. Relative abundance of each Atlantic cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) yearclass was not reflected by egg or larval abundance in any year examined. However, abundance of both pelagic and settled juveniles did appear to ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…Differentiation of the effects of these variables on pelagic juveniles and earlier life-history stages, therefore, is necessary for resolving recruitment variability in marine fish stocks, particularly as year-class strength is considered to be governed by growth and mortality of these initial stages (Cushing 1973, Campana et al 1989, Mertz & Myers 1994. In this study, we found that spawning origins and demographic characteristics of pelagic juvenile cod in Icelandic waters were significantly related to physical transport mechanisms, ambient environmental conditions, food availability, and size of the spawning stock.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of the effects of these variables on pelagic juveniles and earlier life-history stages, therefore, is necessary for resolving recruitment variability in marine fish stocks, particularly as year-class strength is considered to be governed by growth and mortality of these initial stages (Cushing 1973, Campana et al 1989, Mertz & Myers 1994. In this study, we found that spawning origins and demographic characteristics of pelagic juvenile cod in Icelandic waters were significantly related to physical transport mechanisms, ambient environmental conditions, food availability, and size of the spawning stock.…”
Section: Discussionmentioning
confidence: 99%
“…The first problem has been described in detail before (Rothschild, 1986;Ulltang, 1996). Bailey et al (1996) and Campana et al (1989) considered it explicitly when constructing survival curves of walleye pollock as well as Nova Scotia cod and haddock cohorts relative to their physical and biological environment. For the Baltic, however, this type of approach has not yet been conducted.…”
Section: Applicability Of Recruitment Modelsmentioning
confidence: 99%
“…The first problem has been described in detail previously (Rothschild 1986;Ulltang 1996). Bailey et al (1996) and Campana et al (1989) considered it explicitly when constructing survival curves of walleye pollock as well as Nova Scotia cod and haddock cohorts relative to their physical and biological environment. For the Baltic, however, this type of approach has not been conducted (for a discussion of previous stock-recruitment models, see JarreTeichmann et al 2000).…”
Section: Applicability Of Stock-recruitment Modelsmentioning
confidence: 99%